Strength and Durability of Superplasticizer Concrete Based on Different Component Parameters: An Experimental and Statistical Study - Tunc, Esra Tugrul (Springer Heidelberg, 2025)
Concrete, which forms the skeleton of buildings, is the most important building material to ensure the continuity of a building's durability and to survive a possible earthquake. Concrete durability is directly related to its constituent materials. In this study, it was investigated how concrete aggregate and chemical admixture change the strength of concrete according to their type. The research question of this study is: what is the place and importance of aggregate and chemical admixture in increasing concrete strength? Recent earthquakes, especially in Turkey, have shown that most of the buildings that collapsed had poor-quality concrete. The aim of this study is to determine the concrete mix designs for the production of superplasticizer concrete for the production of concrete with the desired strength depending on the tested parameters. In this study, the effect of the parameters that make up the tested concrete content on concrete strength was investigated both experimentally and statistically. Water-cement ratio, aggregate type, Los Angeles abrasion resistance of aggregates, aggregate-cement ratio and new-generation polycarboxylate-supported superplasticizer chemical admixture are the parameters in the concrete content. Statistical analysis was carried out with SPSS, an up-to-date software, using the experimental findings. There was a very good agreement between both measured and predicted values. The equations with a coefficient of determination R 2 > 0.96 were derived. The developed statistical method was found to be unique and highly accurate. Thus, it is aimed to provide safe, economical, practical and time-saving pre-mix designs.
Keywords: Concrete strength; Superplasticizer concrete; Aggregate type; Chemical additive; Statistical model; SPSS software